Antagonistic interaction networks in a native and an exotic legume species in Colombian tropical dry forest - Camacho-Erazo, Mariana; Robles, Jorge; Amarillo-Suárez, Ángela R. (Instituto de Ecología, A.C., 2021)
Plant-animal interactions play a fundamental role in ecosystem functioning and structure. Seed-associated insect communities are expected to be very specific for each plant species due to the large amount of physical and chemical barriers plants impose on the herbivores. In addition, leguminous species, the dominant plant group in the tropical dry forest (TDF), offer a large quantity of resources for insect specialization, structuring specialist communities of herbivorous and parasitoids. However, the introduction of exotic species to TDF may alter the insect associated communities by diminishing diversity and simplifying interactions. By using ecological network analysis, we compared the diversity and structure of the insects associated with seeds and  parasitoids of the native leguminous species Pseudosamanea guachapele (Kunth) Harms and the exotic and invasive leguminous Leucaena leucocephala (Lam.) de Wit. We also evaluated differences in seed chemistry between these species in order to determine to what extent this could help to explain differences in associated insect communities. The study was carried out in a tropical dry forest remnant in the department of Tolima, Colombia. We found seven species of herbivores and eight species of parasitoid insects. The insect interaction networks from both species of plants had low connectance, nestedness, generality, and vulnerability. Leucaena leucocephala had the greatest diversity of herbivores and parasitoid insects compared to P. guachapele, perhaps because Leucaena leucocephala produces seeds all year around, while P. guachapele has marked seasonality, producing fruits only during one or two months of the year. We identified a total of 26 compounds in the seeds of the two hosts. Seeds of P. guachapele have twice the number of compounds than those of Leucaena leucocephala. Among the main differences between the composition of the host plant seeds are the fatty acids that offer different sources of cholesterol for insect development. It may help to explain the presence of species of seed feeders associated with each plant. It is important to notice that the networks described here may change across time and landscapes, making it interesting to continue analyzing the variation in richness and structure of such networks in order to define the extent to which the interactions found in this study remain constant.